2012
DOI: 10.1111/j.1447-0756.2011.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of elastin, fibulin‐5 and lysyl oxidase‐like 1 in the uterosacral ligaments of postmenopausal women with pelvic organ prolapse

Abstract: There was decreased expression of fibulin-5 and LOXL1 in the uterosacral ligaments of patients with pelvic organ prolapse, while the elastin expression was equivalent, which may suggest the possibility of defects in elastic fiber remodeling in the postpartum period and contribute to POP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…10 Research with the Loxl1 KO mouse model in particular is supported by human genetic data implicating abnormal elastin homeostasis in the pathophysiology of POP. 14,28 In addition, POP in Loxl1 KO mice simulates the phenotype of POP in women, with vaginal delivery as a major risk factor, often affecting voiding function, and progressing with age. 1,11,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Research with the Loxl1 KO mouse model in particular is supported by human genetic data implicating abnormal elastin homeostasis in the pathophysiology of POP. 14,28 In addition, POP in Loxl1 KO mice simulates the phenotype of POP in women, with vaginal delivery as a major risk factor, often affecting voiding function, and progressing with age. 1,11,12 …”
Section: Discussionmentioning
confidence: 99%
“…10 Although, no animal model is capable of incorporating all the characteristics and risk factors of POP in women, lysyl oxidase like-1 knockout ( Loxl1 KO) mice develop POP with phenotypic characteristics and risk factors similar to women, although they present a higher incidence of rectal prolapse than humans. 1114 LOXL1 is a metalloenzyme responsible for crosslinking tropoelastin into its functional form, elastin, which provides the extracellular matrix (ECM) with its structure and recoil properties. 15 Similar to women, parity is the leading risk factor for POP in Loxl1 KO mice and POP is delayed, but not prevented, by cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…LOXL1-deficient mice display POP, thinner vaginal wall, and lower urinary tract dysfunction through an inability of urogenital tissues to replenish elastic fibers after parturition (Liu et al, 2006). LOX and LOXL3 protein levels are significantly decreased in POP patients (Alarab et al, 2010;Zhao and Zhou, 2012). LOXL2 mRNA levels are significantly decreased in postmenopausal POP patients compared with asymptomatic postmenopausal controls (Drewes et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…Three studies found reduced LOXL1 expression in pre-menopausal, post-menopausal, or a mixed population of women with POP, suggesting a mechanism of sub-optimal elastin polymerization leading to FPOP. 15,16,17 The group subsequently found increased CpG methylation in the LOXL1 gene promoter in DNA from a mixed population of women with FPOP and lower LOXL1 mRNA levels suggesting a possible epigenetic mechanism. 18 Conversely, Jung et al found increased expression of LOXL1 mRNA in post-menopausal women with FPOP, which they proposed was due to compensatory induction of LOXL1 expression secondary to aberrant cross-linking of tropoelastin.…”
Section: Introductionmentioning
confidence: 99%